Effective Youth Communication in Building Religious-Based Social Awareness - Muhamad Hanif Fuadi; Frista Fitriany Ramadhanita (Communigate, 2025)
This article discusses the role of youth in building religious-based social awareness through effective communication. This study was conducted through community service activities carried out with the Islamic Broadcasting Communication (KPI) Student Association at the Nahdlatul Ulama Institute Tasikmalaya. The focus of the study includes the definition and concept of effective communication, the role of youth in socio-religious issues, integration of religious values in communication, communication strategies, media, and challenges faced. The methods used include group discussions, interactive counselling, and environmental and social studies. The results of the service showed that effective communication with a religious approach can increase understanding, involvement, and real action in solving social issues. Communication approaches that integrate the values of honesty, empathy and fairness strengthen messaging and create deeper emotional connections. Youth play a strategic role as a link between traditional and modern generations through the utilisation of digital media such as Instagram and TikTok, which allows for widespread and interactive dissemination of religious messages. Challenges faced, such as cultural resistance and different interpretations of religious values, can be overcome through collaboration with local communities and the involvement of community leaders as mediators.